Temporal patterns of megalopal settlement in different areas of an East African mangrove forest (Gazi Bay, Kenya) - Ragionieri, Lapo
Most intertidal brachyurans produce planktonic larvae which develop pelagically and, after a certain time in the ocean, migrate towards the habitats that they will eventually settle in. One of the main physical processes affecting larval release and settlement in species inhabiting estuaries and mangroves is the tidal regime. In this study, we investigated whether patterns of settlement of brachyuran larvae at four sites (differing in tidal inundation and crab zonation) of a Kenyan mangrove were affected by the diurnal and lunar cycle of the tide. We collected megalopae at the four sites twice a day throughout two lunar months. Settlement differed at the four sites: at the subtidal site (the main creek within the forest) megalopae arrived during diurnal and nocturnal neap and spring tides, while at the three sites within the forest settlement occurred only at spring tide periods. Specific differences among these latter sites existed in terms of full versus new moon spring tides and, to a smaller extent, with diurnal period. Our results show that larval settlement in mangrove forests takes place at both landward and seaward belts and is a temporally complex event, driven by tidal cycles, but also in synergy with other factors.